Anomalous nuclear overhauser effects in carbon-substituted aziridines: Scalar cross-relaxation of the first kind - Kuprov, I; Hodgson, D; Kloesges, J; Pearson, C; Odell, B; Claridge, T (Wiley, 2015)
Anomalous NOESY cross-peaks that cannot be explained by dipolar cross-relaxation or chemical exchange are described for carbon-substituted aziridines. The origin of these is identified as scalar cross-relaxation of the first kind, as demonstrated by a complete theoretical description of this relaxation process and by computational simulation of the NOESY spectra. It is shown that this process relies on the stochastic modulation of J-coupling by conformational transitions, which in the case of aziridines arise from inversion at the nitrogen center. The observation of scalar cross-relaxation between protons does not appear to have been previously reported for NOESY spectra. Conventional analysis would have assigned the cross-peaks as being indicative of a chemical exchange process occurring between correlated spins, were it not for the fact that the pairs of nuclei displaying them cannot undergo such exchange. Scalar relaxation: Apparently anomalous cross-peaks in 2D 1HNOESY spectra of carbon-substituted aziridines are shown to arise from scalar cross-relaxation of the first kind (SRFK; see picture), due to modulation of scalar coupling constants between protons. Such effects will likely be seen in NOESY spectra of other small molecules experiencing dynamic exchange modulation of scalar 1H-1H coupling constants.